S100a4 Is Secreted by Alternatively Activated Alveolar Macrophages and Promotes Activation of Lung Fibroblasts in Pulmonary Fibrosis - Zhang, Wei; Ohno, Shinji; Steer, Beatrix; Klee, Stephan; Staab-Weijnitz, Claudia A.; Wagner, Darcy; Lehmann, Mareike; Stoeger, Tobias; Königshoff, Melanie; Adler, Heiko (Frontiers in Immunology, 2018)
Idiopathic pulmonary fibrosis (IPF) is a devastating interstitial lung disease, characterized by damage of lung epithelial cells, excessive deposition of extracellular matrix in the lung interstitium and enhanced activation and proliferation of fibroblasts. S100a4, also termed FSP-1 (fibroblast-specific protein-1), was previously considered as a marker of fibroblasts but recent findings in renal and liver fibrosis indicated that M2 macrophages are an important cellular source of S100a4. Thus, we hypothesized that also in pulmonary fibrosis, M2 macrophages produce and secrete S100a4, and that secreted S100a4 induces the proliferation and activation of fibroblasts. To prove this hypothesis, we comprehensively characterized two established mouse models of lung fibrosis: infection of IFN-γR-/- mice with MHV-68 and intratracheal application of bleomycin to C57BL/6 mice. We further provide in vitro data using primary macrophages and fibroblasts to investigate the mechanism by which S100A4 exerts its effects. Finally, we inhibit S100a4 in vivo in the bleomycin-induced lung fibrosis model by treatment with niclosamide. Our data suggest that S100a4 is produced and secreted by M2 polarized alveolar macrophages and enhances the proliferation and activation of lung fibroblasts. Inhibition of S100a4 might represent a potential therapeutic strategy for pulmonary fibrosis.